2020
DOI: 10.9734/cjast/2020/v39i1130650
|View full text |Cite
|
Sign up to set email alerts
|

Metallic Health Risk through Consumption of Different Rice Varieties Cultivated in Industrial Wastewater Irrigated Farmers’ Fields of Bhaluka Area, Bangladesh

Abstract: A study was conducted to assess metallic health risk for population through consumption of rice grown in industrial wastewater irrigated sites of Bhaluka area, Mymensingh. Total 9 rice samples of 3 different varieties (BR-28, BR-29 and Kalozira) were collected directly from the farmers’ fields of the area and analysed for this study. The mean concentration of Zn, Cr, Cu, Ni, Cd, Mn and Fe in rice grains, straw and husk of different rice varieties were 54.46, 12.56, 5.45, 8.01, 1.37, 14.82 and 94.1 µg g-1; 74.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…All of the rice cultivars in this study (except Basmati, Kaligira and Chinigura) have a Cr concentration below the MAC of 1.0 mg/kg [ 29 ]. Zakir et al [ 34 ] observed higher Cr content (10–15 mg/kg) in the rice cultivars obtained from the rice fields of Bhaluka area, Mymensingh, where industrial wastewater was used for irrigation. The differences from the findings of this study could be due to their use of industrial wastewater for irrigation that may have high Cr content.…”
Section: Resultsmentioning
confidence: 99%
“…All of the rice cultivars in this study (except Basmati, Kaligira and Chinigura) have a Cr concentration below the MAC of 1.0 mg/kg [ 29 ]. Zakir et al [ 34 ] observed higher Cr content (10–15 mg/kg) in the rice cultivars obtained from the rice fields of Bhaluka area, Mymensingh, where industrial wastewater was used for irrigation. The differences from the findings of this study could be due to their use of industrial wastewater for irrigation that may have high Cr content.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of Pb and As in rice is different from one source to another [11]. Studies by Naseri et al [10] showed certain amounts of Pb and Cd in local and imported rice grains sold in Shiraz, Lebanon [1]. The presence of Cd may be due to the nature of the soil, fertilizers used, and the quality of the irrigation water [3].…”
Section: Discussionmentioning
confidence: 99%
“…The total production of local paddy rice was estimated at one million tonnes in 2018 compared with 559 tonnes in 2015, which demonstrates an increase of 102% in the past five years. Rice is the main food product consumed in Senegal and has been an important source of heavy metals through absorption effects [10]. Although numerous studies have shown the heavy metal contamination of rice in different countries [11], information is lacking regarding heavy metal contaminants in the rice consumed in Africa [12].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables encompass both vital and non-vital metals over a great variety of concentrations during manufacturing, harvesting, transportation, and selling ( Haque et al., 2021 ), which is enough to create severe health hazards to both animals and humans due to consuming these metals contaminated vegetables ( Sankar et al., 2006 ) Fish and vegetables are the two key food items, which regularly consumed by the Bangladeshi people. Numerous studies ( Aysha et al., 2017 ; Haque et al., 2018 ; Zakir et al., 2020 ) found a high concentration of diverse toxic metals in those foodstuffs. Various diseases may perhaps develop due to the consumption of metals and metalloids contaminated food items by the reduction in immunological defenses, reduced psychological behavior, malnutrition-related illness, and a high occurrence of upper digestive tract ( Zakir et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies ( Aysha et al., 2017 ; Haque et al., 2018 ; Zakir et al., 2020 ) found a high concentration of diverse toxic metals in those foodstuffs. Various diseases may perhaps develop due to the consumption of metals and metalloids contaminated food items by the reduction in immunological defenses, reduced psychological behavior, malnutrition-related illness, and a high occurrence of upper digestive tract ( Zakir et al., 2020 ). Metals and metalloids cannot be degraded or destroyed; they can alter their chemical forms ( Martí-Cid et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%